Plant-based seafood alternatives: Current insights on the nutrition, protein-flavour interactions, and the processing of these foods - Enoch Enorkplim Abotsi; Yashodha Panagodage; Marcia English (Current Research in Food Science)
Fish are an important food source; however, the sustainability of current seafood supplies is a major concern for key stakeholders. The development of plant-based seafood alternatives may be suitable products to alleviate some of the pressures on aquatic ecosystems and help support environmental sustainability. However, the wide-spread adoption of these products weighs heavily on the ingredients used in the formulations which should not only satisfy nutritional and sustainability targets but must also meet consumer approval and functionality. In this review, we highlight recent advances in our understanding of the nutritional quality and sensory challenges in particular flavour (which includes taste and aroma), that have so far proven difficult to overcome in the development of plant-based seafood alternatives. Protein interactions that contribute to flavour development in plant-based seafood alternatives and the factors that impact these interactions are also discussed. We also review the recent advances in the innovative technologies used to improve the texture of products in this emerging food category. Finally, we highlight key areas for targeted research to advance the development of this growing segment of food products.